Experimental investigation on ignition schemes of partially covered cavities in a supersonic flow. (April 2016) - Cai, Zun; Sun, Mingbo; Wang, Hongbo; Wang, Zhenguo
Abstract: In this study, ignition schemes of the partially covered cavity in a scramjet combustor were investigated under inflow conditions of Ma =2.1 with stagnation pressure P 0 =0.7 Mpa and stagnation temperature T 0 =947 K. It reveals that the ignition scheme of the partially covered cavity has a great impact on the ignition and flame stabilization process. There always exists an optimized global equivalence ratio of a fixed ignition scheme, and the optimized global equivalence ratio of ignition in the partially covered cavity is lower than that of the uncovered cavity. For tandem dual-cavities, ignition in the partially covered cavity could be enhanced with the optimization of global equivalence ratio. However, ignition in the partially covered cavity would be exacerbated with further increasing the global equivalence ratio. The global equivalence ratio and the jet penetration height have a strong coupling with the combustion flow-field. For multi-cavities, it is assured that fuel injection on the opposite side could hardly be ignited after ignition in the partially covered cavity even with the optimized global equivalence ratio. It is possible to realize ignition enhancement in the partially covered cavity with the optimization of global equivalence ratio, but it is not beneficial for thrust increment during the steady combustion process.